Experimental investigation of threshold velocities for air-water two-phase flow in a vertical tube and annular channels - Almog Biton; Evgeny Rabinovich; Erez Gilad (Nuclear Engineering and Technology)
This work presents an experimental study of five threshold velocities for air-water flow in three different vertical channels. The measured threshold velocities included onset flooding (OF), end flooding (EF), onset deflooding (OD), end deflooding (ED), and minimum pressure (MP) velocities. The experimental system includes a transparent vertical tube of 52.5 mm inner diameter and 1500 mm length. The test channel can be easily changed from a tube to an annular shape by inserting a cylindrical test element. A counter-current or concurrent upward flow was achieved by blowing air upward from the channel's bottom and flowing water from its top. The threshold velocities were determined by analyzing the pressure drop versus air superficial velocity. Findings revealed evident hysteresis between the end flooding and onset deflooding velocities. In contrast, the end deflooding and onset flooding velocities were found to be identical. The end flooding velocity was indifferent to the water's superficial velocity for all three channel geometries. A generalized gas-liquid flow state diagram for vertical channels is developed based on the present empirical analysis for different threshold velocities.